PENGARUH LAYANAN INFORMASI TENTANG PEMAHAMAN KARIR TERHADAP PERENCANAAN KARIR SISWA KELAS X TKK DAN TKJ SMK NEGERI 4 PEKANBARU - lasmawanti, Resi; Yakub, Elni; asyari, Abu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to; 1) To know the description of career planning before the students are given information about the understanding of career services. 2) To know the description of information understanding the process of career services tar student career planning. 3) To know the description given after the students career planning information services on understanding the career. 4) To determine differences instudents' career planning before and after the understanding of career information services.5) To determine the influence of information services on understanding the career of the students' career planning. The method used is a method Pre-experimental design, by using One group pretest-posttest design. The population was class X TKK and TKJ SMK Negeri 4 Pekanbaru, amounting to 103 people and sample the whole of the population, using sampling techniques saturated. Picture of students' career planning before being given information services are mostly located in the moderate category is 80.58%, and then in the unfavorable category at 11.65% and 7.77% for both categories. Picture of students' career planning after the given information services mostly located in either category, namely 54.37%, while the category of very good 24.27%, medium category at 20.39% 0.97% unfavorable category. Based on the results of the calculation of the correlation coefficient between x1 and x2 is determinant coefficient of 0.57 and r2 = 0.32. This means that the contribution of information on career planning services by 32%. From the calculation of the t-test obtained t greater than ttable (18.5> 1.960) then the hypothesis is accepted, there is a difference between a career planning class X TKK and TKJ SMK Negeri 4 Pekanbaru before and after understanding the information about career services.Keywords: informationservices, career planning